Valors adverbials associats a la conjunció «que»: un estudi històric - Batllori, Montserrat; Suñer, Avel·lina (Caplletra. Revista Internacional de Filologia, 2005)
In this article we will discuss the causal and final adverbial values connected to the conjunction «que» in Catalan and in other Romanic languages. In the first part, we analyse the evolution of the complex conjunctions system in Classical Latin and the posterior oral usages which originated the preliterary Romanic languages. In the second, we study the causal and final subordinate propositions introduced by the nexus «que». As we will try to show, in Medieval Time the nexus que, as it happens today, was used to introduce both argumentative adjuncts, integrated in the predicate, and propositional adjuncts, more external and with a discursive function. Since the 13th century, the progressive substitution of que through other conjunctions will affect causal subordinate and final circumstantial propositions, but otherwise que will maintain its function to introduce discursive causality and finality, specially in oral language.